Brewing a Healthier Future: The Revolutionary Impact of Specialty Coffee on Sugar Consumption in Al Qassim, Saudi Arabia - Maspul, Kurniawan Arif (Innovative: Journal Of Social Science Research, 2023)
This study investigates the culture of specialty coffee and the habit of not adding sugar to coffee, focusing on its impact on sensory perception, public health, and cancer prevention. The study utilizes a qualitative method, conducting in-depth interviews with industry professionals in Saudi Arabia. It covers the journey of specialty coffee from its origin in Jazan, stressing the preservation of distinct flavors and qualities. The study also discusses the potential health advantages of lowering sugar intake through specialty coffee, taking into account geographical variations in sugar consumption trends and the availability of specialty coffee. The necessity of targeted initiatives and policies to promote sugar-free coffee options is underlined. The study also investigates the link between sugar avoidance, cancer prevention, and pertinent theoretical frameworks. Baristas' and coffeepreneurs' opinions reflect a common awareness of the sensory experience and the need of keeping the distinctive flavors of specialty coffee. Overall, the study demonstrates the potential of sugar-free specialty coffee to benefit public health and develop a healthy culture.